Quantitative and modularized CRISPR/dCas9-dCpf1 dual function system in Saccharomyces cerevisiae - Feng, Qing; Ning, Xiaoyu; Qin, Lei; Li, Jun; Li, Chun (Frontiers in Bioengineering and Biotechnology, 2023)
Both CRISPR/dCas9 and CRISPR/dCpf1 genome editing systems have shown exciting promises in modulating yeast cell metabolic pathways. However, each system has its deficiencies to overcome. In this study, to achieve a compensatory effect, we successfully constructed a dual functional CRISPR activation/inhibition (CRISPRa/i) system based on Sp-dCas9 and Fn-dCpf1 proteins, along with their corresponding complementary RNAs. We validated the high orthogonality and precise quantity targeting of selected yeast promoters. Various activating effector proteins (VP64, p65, Rta, and VP64-p65-Rta) and inhibiting effector proteins (KRAB, MeCP2, and KRAB-MeCP2) , along with RNA scaffolds of MS2, PP7 and crRNA arrays were implemented in different combinations to investigate quantitative promoter strength. In the CRISPR/dCas9 system, the regulation rate ranged from 81.9% suppression to 627% activation in the mCherry gene reporter system. Studies on crRNA point mutations and crRNA arrays were conducted in the CRISPR/dCpf1 system , with the highest transcriptional inhibitory rate reaching up to 530% higher than the control. Furthermore, the orthogonal CRISPR/dCas9-dCpf1 inhibition system displayed distinct dual functions, simultaneously regulating the mCherry gene by dCas9/gRNA (54.6% efficiency) and eGFP gene by dCpf1/crRNA (62.4% efficiency) without signal crosstalk. Finally, we established an engineered yeast cell factory for βcarotene production using the CRISPR/dCas9-dCpf1 bifunctional system to achieve targeted modulation of both heterologous and endogenous metabolic pathways in Saccharomyces cerevisiae. The system includes an activation module of CRISPRa/dCas9 corresponding to a gRNA-protein complex library of 136 plasmids, and an inhibition module of CRISPRi/dCpf1 corresponding to a small cr-RNA array library. Results show that this CRISPR/dCas9-dCpf1 bifunctional orthogonal system is more quantitatively effective and expandable for simultaneous CRISPRa/i network control compared to single-guide edition, demonstrating higher potential of future application in yeast biotechnology.